Innovative nonthermal technologies : chlorophyllin and visible light significantly reduce microbial load on basil - Paskeviciute, Egle (Array, 2019)
Due to the high amount of biologically active compounds, basil is one of the most popular herbs. However, several outbreaks have been reported in the world due to the consumption of basil contaminated with different food pathogens. The aim of this study is to apply nonthermal and ecologically friendly approach based on photosensitization for microbial control of basil which was naturally contaminated with mesophils and inoculated with thermoresistant food pathogen Listeria monocytogenes 56Ly. The obtained data indicate that soaking the basil in 1.5·10-4 M chlorophyllin (Chl) for 15 min and illumination with light for 15 min at 405 nm significantly reduced total aerobic microorganisms on basil by 1.3 log CFU/g, and thermoresistant L. monocytogenes 56Ly from 6.1 log CFU/g in control to 4.5 log CFU/g in the treated samples. It is important to note that this treatment had no impact on enzymatic activity of polyphenol oxidase and pectinesterase. Results obtained in this study support the idea that photosensitization technique with its high selectivity, antimicrobial efficiency and nonthermal nature can serve in the future for the development of safe nonthermal and environmentally friendly preservation technology for different fruits and vegetables.